Perfusion Magnetic Resonance Imaging Characteristics of Intracerebral Tuberculomas and Its Role in Differentiating Tuberculomas from Metastases. (April 2013) - Sankhe, Shilpa; Baheti, Akshay; Ihare, Ashish; Mathur, Shobhit; Dabhade, Poonam; Sarode, Ashish
Background: Intracerebral tuberculomas usually manifest as ring-enhancing of nodular lesions on magnetic resonance imaging (MRI). These imaging findings are also observed in other lesions like metastases and toxoplasmosis. Purpose: To study the MRI perfusion characteristics of tuberculomas and its potential role in their definitive diagnosis. Material and Methods: Thirty-four tuberculomas were evaluated by conventional and perfusion MRI. The relative cerebral blood volume (rCBV) values of the center, peripheral wall, and perilesional neuroparenchymal tissue were calculated using rCBV maps. Ten ring-enhancing metastases were similarly evaluated and rCBV values of their peripheral walls were calculated. Results: Thirty-one of the 34 tuberculomas were ring-enhancing or conglomerate lesions and revealed hypoperfused centers with hyperperfused peripheral walls, with the mean rCBV ± SD being 0.42 ± 0.25 and 2.04 ± 0.61, respectively. Three nodular enhancing lesions showed predominantly homogenous hyperperfusion, with the mean rCBV measuring 2.96 ± 0.39 (mean ± SD). The perilesional neuroparenchyma was hypoperfused in both cases. The metastases revealed mean rCBV ratio of the peripheral wall to be 5.43 ± 2.1 (mean ± SD). Analysis of the values by ROC curve method revealed a cut-off value of ≥ 3.745 for differentiating ring-enhancing metastases from ring-enhancing tuberculomas. Conclusion: Perfusion MR is a useful tool for the assessment of tuberculomas and can help differentiate them from neoplasms like metastases. It also has a potential role in monitoring therapy and for early detection of drug resistance.